Cladistic analysis of species of Natalis Laporte (1836) and related genera Eunatalis Schenkling (1909), Metademius Schenkling (1899) and Eurymetomorphon Pic (1950) (Coleoptera: Cleridae: Clerinae) with redescription of a restored Clerinae genus - Solervicens A., Jaime (Zootaxa, 2007)
A cladistic analysis of the species of Natalis Laporte (1836), and related genera Eunatalis Schenkling (1909), Metademius Schenkling (1899) and Eurymetomorphon Pic (1950), is presented. Representatives of the genus Calendyma Lacordaire (1857), are used as the outgroup. The synapomorphies of Eurymetomorphon allow to restore it as a valid generic entity. The synapomorphies shared by Eunatalis and Metademius suggest that these genera constitute a monophyletic group, related to Natalis, but evolved independently in the Australian region. According to this statement it is proposed to restore Eunatalis and Metademius as valid generic entities, but their characterization will require the analysis of a greater number of species. Within the genus Natalis, two monophyletic groups are recognized: one formed by N. laplacei Laporte (1836), the generic type species, and N. wagneri Lesne (1911), and another one composed of N. punctipennis Germain (1855), N. impressus (Spinola 1849), and N. pallidus Solervicens (1976) for which the genus Neogyponyx Schenkling (1906) is revalidated. A redescription of Neogyponyx is provided as is a key to the species.